Analysis of Social Conflicts in Poland’s Soundscape as a Challenge to Socio-Acoustics - Sebastian BERNAT (Archives of Acoustics)
The study objective was to understand the character and location of social conflicts in Poland’s soundscape. The analyses were based on a review of press and Internet articles from the years 2008–2015 and reports on noise, preceded by a review of the legal framework of protection against noise in Poland. Questionnaire surveys concerning Poland’s national parks and health resorts and the city of Lublin were an additional source of information. In the case of the former, the surveys were supplemented with a general examination of the acoustic determinants of social conflicts in the Podzamcze district.